Completed Genome Sequence of the Anaerobic Iron-Oxidizing Bacterium Acidovorax ebreus Strain TPSY - Byrne-Bailey, Kathryne G. (American Society for Microbiology (ASM), 2010)
Acidovorax ebreus strain TPSY is the first anaerobic nitrate-dependent Fe(II) oxidizer for which there is a completed genome sequence. Preliminary protein annotation revealed an organism optimized for survival in a complex environmental system. Here, we briefly report the completed and annotated genome sequence of strain TPSY.